Use of probiotics in newborns: a neonatologist’s perspective - Łoniewska, Beata; Łoniewski, Igor (Pediatria Polska - Polish Journal of Paediatrics, 2025)
The neonatal period is crucial for microbiota development, especially in preterm infants, who face challenges, such as limited maternal contact and medical interventions. While breastfed full-term infants usually develop healthy gut flora naturally, preemies are at risk for conditions, including necrotizing enterocolitis (NEC), feeding intolerance, and sepsis. Probiotics may help reduce these risks. Guidelines from ESPGHAN and AGA cautiously support specific strains for NEC prevention, stressing the importance of strain selection, product quality, and safety. However, risks, such as probiotic-induced sepsis and lack of FDA-approved options, highlight the need for more research. Ethical concerns, informed consent, and close monitoring are essential. This article provided practical, evidence-based guidance for neonatologists, advocating responsible probiotic use to improve outcomes in preterm infants.